THE ANTECEDENT OF EDUCATIONAL STAFF CONTEXTUAL PERFORMANCE IN MEDAN CITY PRIVATE UNIVERSITIES - Supriadi, .; Dalimunthe, Ritha F.; Lumbanraja, Prihatin; Tarmizi, H. B. (Archives of Business Research, 2021)
Resource Based View (RBV) theory appears often used to create models that explain how to achieve firm performance in an effort to win the competition. The level of analysis unit used by the RBV theory base is organization. The issue that arises in this RBV theory is its ability to reach the unit of analysis at the individual or individual level. To become an employee who has contextual performance, requirements are needed, among others, employees have valuable resources, where these resources will be able to exploit opportunities and neutralize threats, have scarce resources among existing employees, cannot be imitated, not equivalent as a substitute. The aim of this study was to determine and analyze the effect of cultural openness, personal and organizational suitability, and organizational climate on partially innovative work behavior. To identify and analyze the effect of cultural openness, personal and organizational suitability, organizational climate and innovative work behavior towards a partially contextual performance. To identify and analyze the effect of cultural openness on contextual performance which mediated by innovative work behavior. To identify and analyze the effect of personal and organizational suitability on contextual performance which mediated by innovative work behavior. To identify and analyze the influence of organizational climate towards contextual performance mediated by innovative work behavior. To identify and analyze the influence of organizational climate towards innovative work behavior moderated by intrinsic motivation. To identify and analyze the influence of organizational climate towards contextual performance moderated by intrinsic motivation.